The role of propensity to moral disengagement in the prediction of non-ethics outcomes at work - Ramos-Villagrasa, Pedro J.; Fernández-del-Río, Elena; Reig-Botella, Adela; Clemente, Miguel (Anales de Psicología / Annals of Psychology, 2024)
There is a strong evidence supporting the influence of propensity to moral disengagement (PMD) on ethical outcomes at work. Complementing previous research, this study analyzes the relationship of PMD with Big Five and Dark Tetrad personality traits, and if PMD predicts outcomes that have no ethical basis but are relevant to organizational success (i.e., task performance, adaptive performance, and work engagement). The design was cross-sectional. A total of 405 employees from different organizations being involved in the study, filling a questionnaire with the variables of interest. All workers voluntarily agreed to participate and were informed about the study, their role as participants, and the confidentiality of their responses. Data were analyzed using descriptive statistics, correlations analysis and hierarchical regression analyses. The results show that: (1) Big Five and the Dark Tetrad are determinants of PMD; (2) PDM predicts task performance, adaptive performance, and work engagement; and (3) if the 'Big Five' and the Dark Tetrad are taken into account in predicting non-ethics outcomes, PDM continues to play a role in explaining task performance and work engagement. However, more research is needed to verify these findings.